2019
DOI: 10.1101/773333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long non-coding RNA Neat1 regulates adaptive behavioural response to stress in mice

Abstract: NEAT1 is a highly and ubiquitously expressed long non-coding RNA (lncRNA) which serves as an important regulator of cellular stress response. However, the physiological role of NEAT1 in the central nervous system (CNS) is still poorly understood. In the current study, we addressed this by characterising the CNS function in the Neat1 knockout mouse model (Neat1 -/mice), using a combination of behavioural phenotyping, electrophysiology and expression analysis. RNAscope® in situ hybridisation revealed that in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…51 This notion has now changed as several studies have been undertaken to more thoroughly investigate their physiology and behaviour at specific physiological circumstances. 21,[74][75][76][77][78][79][80] Most strikingly, female Neat1 ko mice are less fertile than wild type mice and have defects in postnatal mammary gland development that critically interferes with their ability to nurture offspring. 74,75 The compromised fertility may, at least partially, be explained by impaired corpus luteum formation and reduced secretion of progesterone.…”
Section: Physiological Roles Of Neat1mentioning
confidence: 99%
See 1 more Smart Citation
“…51 This notion has now changed as several studies have been undertaken to more thoroughly investigate their physiology and behaviour at specific physiological circumstances. 21,[74][75][76][77][78][79][80] Most strikingly, female Neat1 ko mice are less fertile than wild type mice and have defects in postnatal mammary gland development that critically interferes with their ability to nurture offspring. 74,75 The compromised fertility may, at least partially, be explained by impaired corpus luteum formation and reduced secretion of progesterone.…”
Section: Physiological Roles Of Neat1mentioning
confidence: 99%
“…77 Neat1 ko mice also display behavioural abnormalities that indicate defects within the central nervous system, and cultivated neurons from Neat1 ko mice are hyper excitable and have dysregulated calcium homeostasis. 78,79 NEAT1 is abnormally expressed in many cancers NEAT1 is upregulated in tumour cells compared to normal cells in a wide range of human solid cancers (recently reviewed in 10,[81][82][83] ). In most cases, elevated NEAT1 expression is associated with aggressive disease and poor clinical outcome.…”
Section: Physiological Roles Of Neat1mentioning
confidence: 99%
“…Similar to MALAT1 , also NEAT1 recently proved to play an important role in modulating AS events. Shelkovnikova laboratory, taking advantage of a Neat1 knockout mouse model, demonstrated that the lncRNA controls the AS of a group of genes important for neuronal proliferation and differentiation, cell–cell interactions in the central nervous system (CNS), synaptogenesis, and axon guidance [ 23 ]. Interestingly, Neat1 also controls the AS of a group of RBPs including hnRNPA2B1, hnRNPH1, hnRNPD, hnRNPK, SRSF5, and SRSF7 [ 23 ].…”
Section: Lncrnas Rbps and Regulation Of Pre-mrna Processingmentioning
confidence: 99%
“…Shelkovnikova laboratory, taking advantage of a Neat1 knockout mouse model, demonstrated that the lncRNA controls the AS of a group of genes important for neuronal proliferation and differentiation, cell–cell interactions in the central nervous system (CNS), synaptogenesis, and axon guidance [ 23 ]. Interestingly, Neat1 also controls the AS of a group of RBPs including hnRNPA2B1, hnRNPH1, hnRNPD, hnRNPK, SRSF5, and SRSF7 [ 23 ]. Neat1 knockout mice display a phenotype characterized by deficit in social interaction and rhythmic patterns of CNS activity [ 23 ].…”
Section: Lncrnas Rbps and Regulation Of Pre-mrna Processingmentioning
confidence: 99%
See 1 more Smart Citation